Bacterial cellulose-MOF composite aerogel as well as preparation method and application thereof
By introducing ZIF-8 into the modified cellulose aerogel to form bacterial cellulose-MOF composite aerogel, the problem of insufficient antibacterial performance in food packaging is solved, and the food shelf life is extended and the packaging safety is improved.
Patent Information
- Application Number
- CN202411879965.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art is difficult to effectively inhibit the growth of harmful microorganisms in food packaging, resulting in short shelf life of food and insufficient safety.
By introducing MOF materials, especially ZIF-8, into the modified cellulose aerogel, the bacterial cellulose-MOF composite aerogel is formed, which enhances its antibacterial properties and fresh preservation function.
The composite aerogel significantly improves antibacterial properties, extends the shelf life of food, enhances the safety and stability of packaging, while maintaining good buffering performance and green degradable properties.
Smart Images

Figure CN119708605A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aerogels, and in particular relates to a bacterial cellulose-MOF composite aerogel and a preparation method and application thereof. Background Art
[0002] The development of new packaging materials with stability, cushioning and antibacterial properties is crucial to extend the shelf life of food. Cellulose aerogel is a three-dimensional network structure formed by mutual entanglement of nanocellulose. It stands out in the field of food packaging for its good mechanical properties, cushioning properties and green degradability. In order to effectively inhibit the growth of harmful microorganisms, extend the shelf life of food and improve food safety, the food packaging industry often uses high-efficiency antibacterial materials to achieve the purpose of preservation. Metal-organic framework (MOF) is a new type of organic-inorganic hybrid porous solid material. It has gradually attracted attention due to its advantages such as high porosity, good thermal stability and excellent antibacterial properties. Zeolite imidazolate framework material (ZIF-8) is composed of zinc ions (Zn 2+ ) is a metal organic framework formed by the coordination of 2-methylimidazole (2-MiM). It is one of the most widely studied MOF materials, with good biocompatibility, thermal stability, chemical stability and antibacterial properties. The main antibacterial mechanism of ZIF-8 is that metal ions and some organic ligands can adhere to the surface of bacteria when they come into contact with bacteria, destroying their structural integrity, hindering their metabolism and reproduction, and ultimately leading to their death. This makes ZIF-8 potential in food packaging materials, which can be used to extend the shelf life of food and protect the quality and nutritional content of food. However, the application of MOF aerogel composites in food packaging efficiency or preservation is still in the preliminary research stage, but it has shown great potential. Therefore, this study proposes that the addition of MOF materials to modified cellulose aerogels can make the cushioning packaging more stable while retaining its excellent buffering capacity, improving antibacterial properties and preservation safety functions, which has important application significance for meeting the food industry's demand for packaging materials.
[0003] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing bacterial cellulose-MOF composite aerogel, and the preparation method comprises the following steps:
[0005] (I) Preparation of hydrophobically modified bacterial cellulose aerogel:
[0006] (1) mixing bacterial cellulose with deionized water and then diluting to obtain a bacterial cellulose suspension;
[0007] (2) adding methyltrimethoxysilane into an acidic aqueous solution for hydrolysis to obtain a silica sol;
[0008] (3) mixing the bacterial cellulose suspension and the silica sol, stirring, and then placing in a mold; placing the mold in liquid nitrogen to allow ice crystals to grow, thereby obtaining a frozen sample;
[0009] (4) further freeze-drying the frozen sample to obtain a hydrophobically modified bacterial cellulose aerogel (modified BC aerogel);
[0010] (II) Preparation of bacterial cellulose-MOF composite aerogel:
[0011] (5) dissolving zinc nitrate hexahydrate and 2-methylimidazole in deionized water to obtain a zinc nitrate solution and a 2-methylimidazole solution, respectively;
[0012] (6) immersing the hydrophobically modified bacterial cellulose aerogel in the 2-methylimidazole solution, and then adding the zinc nitrate solution and stirring to obtain a prefabricated composite aerogel;
[0013] (7) The prefabricated composite aerogel is washed and freeze-dried to obtain the bacterial cellulose-MOF composite aerogel (BC / MOF composite aerogel).
[0014] Preferably, in step (1), the concentration of the bacterial cellulose suspension is 0.7 wt %.
[0015] Preferably, in step (2), the acidic aqueous solution is an acetic acid aqueous solution or a hydrochloric acid aqueous solution;
[0016] And / or, the hydrolysis time is 30 min.
[0017] Preferably, in step (3), the stirring method is: magnetic stirring at room temperature for 2 hours.
[0018] Preferably, in step (4), the freeze-drying conditions are: freeze-drying for 72 hours at -92°C and 0.74 Pa.
[0019] Preferably, in step (6), the soaking time is 2 hours;
[0020] And / or, the stirring temperature is 25° C., and the stirring time is 0.5 to 6 hours.
[0021] Preferably, in step (7), the freeze-drying time is 36 hours.
[0022] Based on the same technical concept, another embodiment of the present invention is to provide a bacterial cellulose-MOF composite aerogel obtained by the above preparation method.
[0023] Based on the same technical concept, another solution of the present invention is to provide an application of bacterial cellulose-MOF composite aerogel in the preparation of fresh-keeping packaging products.
[0024] The beneficial effects of the present invention are:
[0025] The present invention prepares BC / MOF composite aerogel by in-situ growth method. SEM shows that the pores of the modified aerogel are orderly arranged, the pore size becomes smaller, and ZIF-8 can be seen loaded on the surface of the aerogel. FTIR and XRD structurally prove that the silane group of MTMS is introduced and ZIF-8 grows in-situ on the BC / MOF aerogel.
[0026] In addition, after loading ZIF-8, the water contact angle of the composite aerogel decreased, but with the increase of the content of loaded ZIF-8, the hydrophobicity of the BC / MOF composite aerogel gradually increased, and the UV shielding gradually increased; the thermal stability of the BC / MOF composite aerogel increased. The antibacterial effect of the BC / MOF composite aerogel gradually increased with the extension of the loading time of ZIF-8, especially the inhibition effect of the BC / MOF composite aerogel on Botrytis cinerea was the best. Except for the BC / MOF-6 composite aerogel, the degradation rate of all aerogels was higher than 80% after 90 days of burial.
[0027] The BC / MOF composite aerogel of the present invention shows excellent application potential in the field of fresh-keeping packaging products, for example, it has great advantages in prolonging the freshness of fruits such as grapes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is the microscopic morphology of the aerogel sample.
[0030] Figure 2 It is the infrared spectrum of the aerogel sample.
[0031] Figure 3 is the X-ray diffraction pattern of the aerogel sample.
[0032] Figure 4 It is the TG curve of the aerogel sample.
[0033] Figure 5 It is the DTG curve of the aerogel sample.
[0034] Figure 6 It is the contact angle data of aerogel sample.
[0035] Figure 7 It is the UV transmittance data of aerogel samples.
[0036] Figure 8 This is the antibacterial effect diagram of the aerogel sample.
[0037] Fig. 9 This is the degradation effect diagram of the aerogel sample. DETAILED DESCRIPTION
[0038] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0039] In the examples, the main chemical reagents, experimental instruments and equipment used are shown in Tables 1 and 2.
[0040] Table 1 Experimental chemical reagents
[0041]
[0042]
[0043] Table 2 Experimental instruments and equipment
[0044] name model Manufacturer Analytical Balance ME204E Mettler Toledo International Inc. Blast drying oven GZX-9140 Shanghai Boxun Industrial Co., Ltd. Freeze Dryer LGJ-50FD Henan Brothers Equipment Co., Ltd. Scanning electron microscopy JSM-5600LV nippon electron optics co., ltd. X-ray diffractometer DX-2700 Haoyuan Instruments Fourier Transform Infrared Spectrometer IS50 Nicolet Corporation Tensile testing machine SMT-5000 Yangzhou Saisi Testing Equipment Co., Ltd. Thermogravimetric Analyzer STA409C / PC Netzsch, Germany Water contact angle tester NBSIOSA60 Ningbo New Boundary Scientific Instrument Co., Ltd. UV spectrophotometer UV752N Shanghai Help International Trading Company
[0045] Example 1
[0046] This embodiment provides a method for preparing bacterial cellulose-MOF composite aerogel, and the preparation method comprises the following steps:
[0047] (1) diluting a bacterial cellulose (BC) dispersion in deionized water to prepare a BC suspension having a concentration of 0.7 wt% and a mass of 20 g;
[0048] (2) Add 280 μL of methyltrimethoxysilane (MTMS) to a 5×10 -3 mol / L acetic acid aqueous solution, and hydrolyzed for 30 min to obtain completely hydrolyzed MTMS silica sol;
[0049] (3) 20 g of BC suspension and MTMS silica sol were magnetically stirred at room temperature for 2 h and then poured into a mold; the bottom of the copper plate was then immersed in liquid nitrogen, and the entire mold was placed on the surface of the copper plate to form a temperature gradient from bottom to top, which promoted the growth of ice crystals from bottom to top along the temperature gradient to obtain a frozen sample;
[0050] (4) freeze-drying the frozen sample at -92°C and 0.74 Pa for 72 h to obtain modified bacterial cellulose aerogel;
[0051] (5) 6 g of zinc nitrate hexahydrate and 13.2 g of 2-methylimidazole were completely dissolved in 280 mL of deionized water to obtain a zinc nitrate solution and a 2-methylimidazole solution, respectively;
[0052] (6) immersing the modified bacterial cellulose aerogel in a 2-methylimidazole solution for 2 h, then adding a zinc nitrate solution and stirring at 25 °C for 0.5 h to obtain a prefabricated composite aerogel;
[0053] (7) The prefabricated composite aerogel was rinsed three times with deionized water to remove residual surface impurities, and finally placed in a freeze dryer for 36 h to obtain bacterial cellulose-MOF composite aerogel.
[0054] Note: The product obtained in this example is named BC / MOF-0.5, where "0.5" means that the stirring time in step (6) is 0.5 h (similar naming method is used hereinafter).
[0055] Example 2
[0056] This embodiment provides a method for preparing bacterial cellulose-MOF composite aerogel, which is different from Embodiment 1 in that in step (6), the stirring time is 1 hour, and the other operations are the same.
[0057] The product obtained in this example is named BC / MOF-1.
[0058] Example 3
[0059] This embodiment provides a method for preparing bacterial cellulose-MOF composite aerogel, which is different from Embodiment 1 in that in step (6), the stirring time is 3 h, and the other operations are the same.
[0060] The product obtained in this example is named BC / MOF-3.
[0061] Example 4
[0062] This embodiment provides a method for preparing bacterial cellulose-MOF composite aerogel, which is different from Embodiment 1 in that in step (6), the stirring time is 6 hours, and the other operations are the same.
[0063] The product obtained in this example is named BC / MOF-6.
[0064] Test example: Structural characterization and performance analysis of BC / MOF composite aerogel
[0065] 1. Scanning electron microscopy
[0066] The aerogel sample was placed in liquid nitrogen for brittle fracture and then cut into 2mm×2mm sections. Then, it was gold-sprayed and placed on an electron microscope test bench. The sample was observed using a scanning electron microscope, with the image magnification set between 5000 and 10000 times.
[0067] (ii) Fourier transform infrared spectroscopy
[0068] Before testing, the aerogel samples were first dried thoroughly in an oven to completely remove moisture. They were then chopped up and mixed with granular potassium bromide. The mixture was stirred with a grinding rod until it was homogeneous, and then crushed and refined until it was in powder form. The powder was evenly spread on a tablet press to prepare uniform flakes, which were then dried to remove residual moisture. After the preparation work was completed, the samples were tested using an infrared spectrometer.
[0069] (III) X-ray diffraction
[0070] Start the instrument, evenly coat the aerogel sample on a glass slide, and place it in the X-ray diffractometer. Set the 2θ range to 5-60° and the scanning rate to 5° / min to perform chemical structure analysis on the aerogel.
[0071] (IV) Thermal stability
[0072] After the aerogel samples were dried under vacuum to remove moisture, thermogravimetric analysis was performed. The test conditions were a nitrogen atmosphere with a temperature range from room temperature to 600°C at a heating rate of 10°C / min.
[0073] (V) Hydrophobic properties
[0074] Make sure the surface of the aerogel sample is smooth and free of impurities or dirt to ensure the accuracy of the measurement. Fix the prepared aerogel sample on the measuring table to ensure that it is horizontal and the surface is fully exposed. Then zero the instrument, use a micro-syringe to drop 3μL of water on the aerogel surface, and finally use a camera to capture an image of the water droplet in contact with the aerogel surface.
[0075] (VI) UV transmittance
[0076] Prepare the aerogel sample and prepare it into the appropriate shape and size for loading into the UV spectrophotometer for measurement. Load the prepared aerogel sample into the sample chamber of the UV spectrophotometer. Make sure the surface of the sample is smooth to ensure that the light can pass through the sample evenly. Before measuring the sample, perform a baseline calibration. Choose a suitable range of 200-800nm for measurement. Calculate the transmittance of the aerogel sample through the known absorbance value.
[0077] (VII) Biodegradability
[0078] In order to gain a preliminary understanding of the degradation time of aerogels, a biodegradability study was conducted. Aerogel samples were cut into 5×7 cm shapes and then buried in the soil at a depth of 10 to 15 cm, and water was sprayed regularly to keep the soil moist. Every 6 days, the aerogels were taken out and photographed to record their morphological changes.
[0079] (VIII) Antibacterial performance
[0080] The antibacterial activity of the aerogels was evaluated by disk diffusion method. First, the concentration of Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, and Salmonella enterica was adjusted to 10 6 ~10 7 CFU / mL. Subsequently, 100 μL of bacterial solution was dropped on the solid culture medium and evenly spread. Subsequently, the circular aerogel with a diameter of 10 mm was rinsed with sterile water and placed on the culture medium for constant temperature culture for 48 h. Finally, the antibacterial effect of the composite aerogel was evaluated by measuring the diameter of the inhibition zone.
[0081] The aerogel was cut into 10×10 mm squares and placed in a solid culture medium. Then, the hyphae of Botrytis cinerea were evenly spread over the entire plate in an ultra-clean workbench. Subsequently, a punch sampler with a diameter of 5 mm was used to remove the fungus block equidistant from the center point and placed on the aerogel. The culture dish was placed in an incubator at 25°C and incubated. On the 7th day, the diameter of the Botrytis cinerea plaque was measured.
[0082] (IX) Data Statistics and Analysis
[0083] All experiments were performed at least three times unless otherwise specified, and the results are expressed as mean ± standard deviation. Microsoft Excel 2016 was used to process the data, and origin 8.5 software was used to draw the graphs. All data were analyzed using AVONA in IBM SPSS Statistics 25, where different lowercase letters indicate significant differences between different treatment groups, i.e., p < 0.05 was considered to be statistically significant.
[0084] Results and Discussion
[0085] (I) Microstructure of BC / MOF composite aerogel
[0086] Observing aerogels using SEM can reveal their microstructure and surface morphology, including pore distribution, morphology, connectivity and other information. This is of great significance for optimizing the aerogel preparation process and evaluating its performance and application. Taking the sample obtained in the preparation process of Example 4 as an example, the SEM image of the aerogel sample is as follows: Figure 1 As shown, it can be seen that BC aerogel ( Figure 1 On the far left, the unmodified pure BC aerogel has a fibrous network structure. These fibrous materials are arranged in a staggered manner to form a porous structure with a large pore size. From the cross-sectional view of the BC aerogel, it is observed that the fibers are squeezed together. Because the strength of the aerogel is extremely low at this time, it is easy to collapse; the modified BC aerogel ( Figure 1 Compared with pure BC aerogel, its microscopic morphology has changed significantly, and the overall structure is axially oriented. From the cross-sectional view, it can be seen that the diameter of the pore structure has become smaller, the three-dimensional network structure has become more uniform, and a honeycomb structure has appeared, which proves that the silane group of MTMS has been successfully introduced to enhance the mechanical properties. From BC / MOF-6 ( Figure 1 In the figure on the far right, it can be observed that its surface is flatter than that of the modified BC aerogel, proving that ZIF-8 grows in situ on the aerogel and is evenly distributed. The aerogel still maintains a three-dimensional network structure and the basic structure has not changed.
[0087] (II) Fourier infrared spectrum of BC / MOF composite aerogel
[0088] Figure 2 The infrared spectrum of BC aerogel is shown. -1 The peak associated with -OH group was observed at 1601 cm -1 and 1351cm -1 The characteristic peaks at 2900cm represent the bending vibrations of OH and CH. -1 The peak at 1032 cm is the stretching vibration of CH. -1The peak at 799 cm is related to the vibration of the side group of the glycoside ring, and there are some weak shoulder peaks around it. The infrared spectrum of the modified BC aerogel is compared with that of the unmodified BC aerogel. -1 A new diffraction peak appeared at 1461 cm-1. This phenomenon is attributed to the asymmetric stretching vibration of Si-O-Si, indicating that MTMS reacted with BC and successfully formed polysiloxane. Compared with the infrared spectrum of the modified BC aerogel, the spectrum of the BC / MOF composite aerogel has a peak at 1461 cm-1. -1 A new characteristic peak appeared at , which was caused by the planar stretching of the imidazole ring, further confirming the successful loading of ZIF-8 onto the aerogel.
[0089] (III) X-ray diffraction of BC / MOF composite aerogel
[0090] For porous materials such as aerogels, XRD can help determine whether a crystal structure exists and the effect of the crystal structure on the properties of the material. It can be used to determine the presence and relative content of various components in the aerogel. Figure 3 It is the X-ray diffraction spectrum of aerogel. It can be seen from the figure that the XRD spectrum diffraction peaks of the four groups of BC / MOF composite aerogels are almost the same. As the loading time of ZIF-8 increases, the BC substrate is covered by ZIF-8, so the peak intensity of the cellulose type I characteristic peak (110, 2θ = 14.5°) weakens. When the ZIF-8 loading time gradually increases, the most important characteristic crystal diffraction peak of ZIF-8 appears, and the diffraction peak intensity increases. The crystal planes are (011, 2θ = 7.1°), (022, 2θ = 14.5°), and (222, 2θ = 17.9°), indicating that ZIF-8 is successfully loaded into BC-MTMS aerogel.
[0091] (IV) Thermal stability of BC / MOF composite aerogels
[0092] TGA can evaluate the mass change of aerogel during heating and thus determine its thermal stability, which is crucial for determining the application range and stability of aerogel at high temperatures. Figure 4-5It can be seen that the thermal decomposition behavior of the five aerogels can be roughly divided into four stages; the first stage is 50℃~200℃, and the mass loss of the aerogels in this stage is less than 10%. The reason for this loss is that the aerogels lose free water and bound water. The second stage is 200℃~350℃, and the aerogels in this stage have the largest mass loss (40%~60%), which is caused by the degradation of the side chain groups in the aerogels. The third stage is 350℃~600℃, and the mass loss of BC aerogel is about 5%. The degradation in this stage is caused by the breakage of the carbon chain, while the mass loss of the aerogel loaded with ZIF-8 is about 15%, because the collapse of the ZIF-8 framework causes decomposition. It can be seen from the figure that the thermogravimetric curves of the five aerogels before and after modification are similar, and after loading ZIF-8, the maximum mass loss temperature is increased, which proves that loading ZIF-8 will increase the thermal stability of the aerogel.
[0093] (V) Hydrophobic properties of BC / MOF composite aerogels
[0094] The hydrophobicity of packaging materials can effectively block the penetration of moisture, oxygen and other gases, thereby extending the shelf life of food. Moisture and oxygen are one of the main factors that cause food spoilage and oxidation, so blocking their penetration is essential to maintaining the freshness and quality of food. Figure 6 It can be seen that the water contact angle of pure BC aerogel is 0°, and it can be completely wetted by water droplets within 3s. This is because BC has a large number of hydroxyl groups, so it shows strong hydrophilicity when it is not modified. After hydrophobic modification, the water contact angle of BC aerogel is 127.2°, and water droplets cannot wet the aerogel. This is because after silane modification, the hydrophilic groups of the aerogel are reduced and the hydrophobic groups are increased, showing obvious hydrophobic properties. This result shows that MTMS is successfully grafted on the surface of the aerogel. After the aerogel surface is loaded with ZIF-8, its water contact angle shows a downward trend. This phenomenon is because the roughness of the aerogel surface is increased, and the rough surface has better wettability to water, which will cause the water contact angle to decrease. As the in-situ growth time of ZIF-8 increases, the content of loaded ZIF-8 gradually increases, making the pore structure on the aerogel surface more ordered or dense, resulting in the diffusion of water molecules on the surface being hindered, thereby increasing the water contact angle.
[0095] (VI) UV transmittance of BC / MOF composite aerogel
[0096] The main role of UV shielding for aerogel packaging is to protect the items in the package from UV damage, extend their shelf life, maintain the appearance of the items, avoid fading, deterioration and degradation, and improve product quality and value. It is especially suitable for items that are sensitive to UV rays, such as medicines, cosmetics and food. Packaging materials with good UV shielding properties can maintain the nutrients and natural pigments in the food and keep its original taste. Figure 7 As shown, BC aerogel shows a high transmittance of 36.7% for ultraviolet radiation in the range of 200nm to 420nm, that is, it has a low ultraviolet shielding property. When loaded with ZIF-8, the four aerogels can block more than 70% of ultraviolet rays. As the loading time increases, the ultraviolet transmittance of the aerogel decreases, among which BC / MOF-6 has the lowest transmittance of 23.8%. This is because the lattice structure of ZIF-8 is relatively stable and has high thermal and chemical stability. This stability makes ZIF-8 less likely to undergo structural damage or dissolution under ultraviolet irradiation, thereby maintaining its shielding performance against ultraviolet rays. At the same time, ZIF-8 has certain optical properties, which can absorb or scatter ultraviolet rays when exposed to them, thereby reducing ultraviolet penetration, proving that ZIF-8 has a good effect on blocking ultraviolet rays.
[0097] (VII) Antibacterial properties of BC / MOF composite aerogels
[0098] The role of antibacterial performance analysis for aerogel packaging is to improve the hygiene and safety of packaging. By evaluating the antibacterial performance of aerogel packaging, the reproduction of bacterial flora in the package can be effectively inhibited, the risk of microbial contamination of susceptible products such as food and medicines can be reduced, their shelf life can be extended, product quality and safety can be ensured, and the market demand for high quality and high hygiene standards can be met. The antibacterial activity of the composite aerogels loaded with ZIF-8 and pure BC aerogels was evaluated by the corresponding methods. The inhibitory effects of the four composite aerogels and pure BC aerogels on Salmonella, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli and Botrytis cinerea are shown in Figure 2. Figure 8As shown. The observation results show that pure BC aerogel has no inhibitory effect on the five tested bacteria, while the composite aerogel loaded with ZIF-8 shows a significant antibacterial effect. As the loading time of ZIF-8 increases, the diameter of the inhibition zone gradually expands, indicating that its antibacterial effect gradually increases. This is because zinc ions can penetrate the cell membrane gap, interact with sulfhydryl and disulfhydryl groups in enzymes, or attach to the negatively charged bacterial cell wall, causing cell rupture during metabolism and ultimately cell death. The composite aerogel has the best inhibitory effect on Botrytis cinerea. The reason is that ZIF-8 usually has a high hydrophobicity, which will have an adverse effect on the growth environment of Botrytis cinerea. Its hydrophobicity may reduce the attachment and growth of Botrytis cinerea on its surface; another reason is that the metal ions released by ZIF-8 may cause changes in the pH value of the surrounding environment, and the growth and reproduction of Botrytis cinerea may be affected by the sensitivity of the environmental pH. It is proved that it can effectively target pathogens that cause grape corruption and can be used as an antibacterial packaging material in the process of grape preservation.
[0099] (VIII) Biodegradability of BC / MOF composite aerogels
[0100] The biodegradability test evaluates the decomposition rate and extent of aerogel packaging in organisms or under specific environmental conditions. This helps determine the environmental friendliness and sustainability of packaging, reduce plastic pollution, promote the use of biodegradable materials, and meet sustainable development goals. The landfill degradation method was used to evaluate the biodegradability of composite aerogels in the natural environment. Fig. 9 It can be seen that after 18 days of burial, pure BC aerogel showed a high degradation rate. This is because BC is derived from cellulose synthesized during bacterial fermentation. It is a natural biopolymer material that is closer to natural materials in structure and composition and is more easily recognized and degraded by soil microorganisms. Microorganisms can secrete corresponding enzymes to decompose cellulose molecules and degrade them into smaller organic matter, thereby promoting the degradation of BC aerogel. In contrast, the aerogel loaded with ZIF-8 has a tighter bond between cellulose chains, a stronger hydrophobicity, and a stronger antibacterial property, making the aerogel surface less susceptible to microbial attachment. After 90 days of burial, the degradation rate of all aerogels exceeded 80%, except for BC / MOF-6, which was slightly lower. This may be because the content of ZIF-8 loaded in BC / MOF-6 is relatively high, and its strong antibacterial property makes it less affected by microorganisms, thus slowing down its degradation rate.
[0101] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing bacterial cellulose-MOF composite aerogel, characterized in that: The preparation method comprises the following steps: (I) Preparation of hydrophobically modified bacterial cellulose aerogel: (1) mixing bacterial cellulose with deionized water and then diluting to obtain a bacterial cellulose suspension; (2) adding methyltrimethoxysilane into an acidic aqueous solution for hydrolysis to obtain a silica sol; (3) mixing the bacterial cellulose suspension and the silica sol, stirring the mixture, and then placing the mixture in a mold; and then placing the mold in liquid nitrogen to allow ice crystals to grow, thereby obtaining a frozen sample; (4) further freeze-drying the frozen sample to obtain a hydrophobically modified bacterial cellulose aerogel; (II) Preparation of bacterial cellulose-MOF composite aerogel: (5) dissolving zinc nitrate hexahydrate and 2-methylimidazole in deionized water to obtain a zinc nitrate solution and a 2-methylimidazole solution, respectively; (6) immersing the hydrophobically modified bacterial cellulose aerogel in the 2-methylimidazole solution, and then adding the zinc nitrate solution and stirring to obtain a prefabricated composite aerogel; (7) The prefabricated composite aerogel is washed and freeze-dried to obtain the bacterial cellulose-MOF composite aerogel.
2. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (1), the concentration of the bacterial cellulose suspension is 0.7 wt %.
3. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (2), the acidic aqueous solution is an acetic acid aqueous solution or a hydrochloric acid aqueous solution; And / or, the hydrolysis time is 30 min.
4. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (3), the stirring method is: magnetic stirring at room temperature for 2 hours.
5. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (4), the freeze-drying conditions are: freeze-drying for 72 hours at -92°C and 0.74 Pa.
6. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (6), the soaking time is 2 hours; And / or, the stirring temperature is 25° C., and the stirring time is 0.5 to 6 hours.
7. The method for preparing bacterial cellulose-MOF composite aerogel according to claim 1, characterized in that: In step (7), the freeze-drying time is 36 hours.
8. The bacterial cellulose-MOF composite aerogel obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the bacterial cellulose-MOF composite aerogel according to claim 8 in the preparation of fresh-keeping packaging products.
Citation Information
Patent Citations
Method for synthesizing ZIF-8 aerogel on basis of cellulose hard template
CN104629080A
Preparation method of super-hydrophobic cellulose aerogel and application of super-hydrophobic cellulose aerogel in oil stain treatment
CN104710647A
Hydrophobic modification method of nanocellulose
CN107383212A
ZIF-8 / bacterial cellulose composite sponge, preparation method thereof and application of ZIF-8 / bacterial cellulose composite sponge as dressing
CN117683269A
Nanofiber composite aerogel as well as preparation method and application thereof
CN118767882A